Antibody–drug conjugates for lung cancer in the era of personalized oncology. (February 2021) - Ricciuti, Biagio; Lamberti, Giuseppe; Andrini, Elisa; Genova, Carlo; De Giglio, Andrea; Bianconi, Vanessa; Sahebkar, Amirhossein; Chiari, Rita; Pirro, Matteo
Abstract: With 9.6 million deaths in 2018, cancer represents one of the most common causes of death, both in men and women. Despite recent advances in the understanding of molecular mechanisms involved in cancer development and progression, treatment options are still limited. Limitations of traditional chemotherapy include the lack of selectivity and the unfavorable safety profile. The efficacy of targeted therapies ( e.g., tyrosine kinase inhibitors) is also limited by their cytostatic action, which inhibits tumor cell proliferation without inducing tumor cell death, and by the risk of acquired resistance. Antibody-drug conjugates (ADCs), a newly developed class of engineered anticancer drugs, consist of recombinant monoclonal antibodies against tumor-specific antigens that are covalently bound to cytotoxic agents. They have been designed to overcome the limitations of traditional chemotherapy and targeted therapies by combining the target selectivity of monoclonal antibodies with the high potency of cytotoxic drugs. Currently, ADCs that have received regulatory approval include brentuximab vedotin for CD30-positive Hodgkin lymphoma and trastuzumab emtansine for human epidermal growth factor receptor 2-positive breast cancer. However, over 80 novel ADCs are actively being investigated in preclinical studies and early-phase clinical trials. In this review, we will provide a comprehensive overview of the biological rational, efficacy and safety of ADCs as therapeutic agents against non-small cell lung cancer and small cell lung cancer.